2013
DOI: 10.1177/1355819613486465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physicians’ gender on communication and consultation length: a systematic review and meta-analysis

Abstract: Objective: Physician gender may be a source of differences in communication between physicians and their patients, which may in turn contribute to patient satisfaction and other outcomes. Our aim was to review systematically research on gender differences in the length, style and content of communication with patients. Methods: Seven electronic databases were searched from inception to September 2010 with no language restrictions (included MEDLINE; PsychINFO; EMBASE; CINAHL; Health Management Information Conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 33 publications
1
108
2
12
Order By: Relevance
“…Differences in communication during medical consultations and longer consultation times have been reported, [3][4][5][6][7] but none of these studies are from a UK hospital setting. 7 Earlier observational studies from the US and Sweden suggest that a complex social system may influence the working lives of male and female doctors differently, with female doctors torn between behaving according to stereotypically 'feminine' traits of being a woman and the 'masculine' stereotype of being a doctor. 8,9 Since these studies were undertaken, the gender composition of the medical workforce has changed substantially, with estimates suggesting women will soon comprise over half of the UK medical workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in communication during medical consultations and longer consultation times have been reported, [3][4][5][6][7] but none of these studies are from a UK hospital setting. 7 Earlier observational studies from the US and Sweden suggest that a complex social system may influence the working lives of male and female doctors differently, with female doctors torn between behaving according to stereotypically 'feminine' traits of being a woman and the 'masculine' stereotype of being a doctor. 8,9 Since these studies were undertaken, the gender composition of the medical workforce has changed substantially, with estimates suggesting women will soon comprise over half of the UK medical workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Having better patient management of female doctors due to good communication are known. 9 In a meta-analytic review, Roter et al found that female doctors engage in more positive talk (such as encouragement), ask more psychosocial questions, discuss more about emotions and demonstrate more partnership building behaviours. 10 By providing appropriate communication and assisting others with health and community care services, pediatricians may increase strong attachment with the patients and his/her family.…”
Section: Discussionmentioning
confidence: 99%
“…• Patient-centered communication (including patients as partners in care and sharing some decision-making) [12][13][14][15][16] • Psychosocial counseling (asking more psychosocial questions, offering encouragement and reassurance) 14 • More time with patients 14,16 Despite these recognized differences in practice, however, did patient outcomes differ between male and female physicians?…”
Section: Background: Process Differences In Practice Patterns Of Femamentioning
confidence: 99%